2017
DOI: 10.17225/jhp00094
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden in haemophilia: results from a single UK centre

Abstract: Haemophilia caregivers face limitations in their life leading to perceived burden. This single-centre study investigates the impact of burden on caregivers’ health-related quality of life (HRQoL). Methods: Questionnaires for caregivers comprised demographic data, HRQoL (EQ-5D, SF-36) and caregiver burden (IOF: Impact on Family Scale). Children were also asked about their HRQoL (EQ-5D, Haemo-QoL Short Form). Results: 20 consecutive parent/child dyads participated. 80% were mothers (mean age of 39.80±6.2 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…40% of those working part‐time did so because of their child's haemophilia, yet only 26.5% reported that this caused an economic impact. In a single‐centre study in the UK, similar results were found for working part‐time due to the child's haemophilia (50%), and by contrast in the UK study, a higher percentage of caregivers reported an economic impact (55%) related to haemophilia . In another study comparing the working situation of caregivers from Sweden, UK and Canada, 46% of caregivers of children with inhibitors worked full‐time compared to 59.5% of caregivers of children with haemophilia and 62.7% of caregivers of healthy children .…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…40% of those working part‐time did so because of their child's haemophilia, yet only 26.5% reported that this caused an economic impact. In a single‐centre study in the UK, similar results were found for working part‐time due to the child's haemophilia (50%), and by contrast in the UK study, a higher percentage of caregivers reported an economic impact (55%) related to haemophilia . In another study comparing the working situation of caregivers from Sweden, UK and Canada, 46% of caregivers of children with inhibitors worked full‐time compared to 59.5% of caregivers of children with haemophilia and 62.7% of caregivers of healthy children .…”
Section: Discussionmentioning
confidence: 53%
“…This impacts not only on the health‐related quality of life (HRQoL) of haemophilia patients, but also their caregivers . Khair et al also described that haemophilia has an economic impact on caregivers’ HRQoL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A UK study in 20 caregivers of children with haemophilia revealed that economic impact and chronic disease of the caregiver affected their HRQoL . The National Health Service in the UK accepts caregiver burden as an important outcome measure in long‐term conditions .…”
Section: Introductionmentioning
confidence: 99%